A Sarong for Clio Essays on the Intellectual and Cultural History of Thailand : Inspired by Craig J. Reynolds - Peleggi, Maurizio (Studies on Southeast Asia series, 2015)
The writings gathered here revolve around two prominent themes in Reynolds's scholarship: the nexus of historiography and power, and Thai political and business cultures--often so intertwined as to be difficult to separate. The chapters examine different types of historical texts, Thai political discourse and political culture, and the media production of consumer culture.